Antibacterial activity of ZygophllumfabagoL. Leaves extracts - Mohammed, Nihad T; Zeki, Lua,lua,aS; Majeed, Isra,a A (Al-Nahrain Journal of Science, 2013)
الخلاصة: The present research consist of qualitative chemical analysis for both aqueous and alcoholic extracts of Zygophyllumfabagoleaves which showed that the glycosides, alkaloids, flavonoids, terpens and steroids were found in both extracts, while saponines and phenolic compounds were found in alcoholic extract only, and both extracts contain no tannins. The other part of research was the determination of the antimicrobial activity of these extracts against eight species of pathogenic bacteria (Esherichia coli, Klebsilla Pneumonia, Proteus volgaris, Proteus mirabilis, Salmonella Sp., Pseudomonas aeruginosa, Streptococcus Pyogens, Staphyllococcusaureus) with six different concentration began with 40 mg/ml to 100 mg/ml by using agar well diffusion method which showed that alcoholic extracts more effective than aqueous ones and that both Staphyllococcousaureusand Escherishia coli were the most affected species.